Penggunaan Hak Memilih Suku Anak Dalam Muara Kilis Jambi dalam Pemilu Presiden dan Wakil Presiden Tahun 2014 (Studi Kasus : Peran Jenang Suku Anak Dalam Muara Kilis) - wulandari .; nur hidayat sardini; fitriyah . (Journal of Politic and Government Studies, 2016)
Suku Anak Dalam is a remote traditional community that exists within theJambi’s forest. Forest exploration and exploitation, which getting higher thesedays, limits the room for a movement and pushes the Suku Anak Dalam habitat.They have to settle and assimilate like the normal society. One of the tribes isSuku Anak Dalam in Muara Kilis Village, Tebo Sub-Province, Province of Jambi.At the year of 2014, Indonesia held a Presidential and Vice PresidentialElection. For the first time, the Suku Anak Dalam participated in Election fromthe first stage until the last stage. They got the suffrage and were listed in the FinalVoter List. This research’s purpose is to find out about the suffrage usage by SukuAnak Dalam at Muara Kilis Village, Tengah Ilir Sub-district, Tebo Sub-Province,Province of Jambi in Presidential and Vice Presidential Election year 2014. Casestudy : the role of Jenang Suku Anak Dalam.The author used qualitative method for the research by collecting the datawhich are interview and documentation. The source came from primary data andsecondary data. The subject of the research was the Members of Suku AnakDalam, Temenggung of Suku Anak Dalam, Jenang of Suku Anak Dalam, PelitaKita Community, and Muara Kilis’ Village Secretary.As can be seen from the backgrounds and the research methods that theauthor used, the result is Suku Anak Dalam does not understand the purpose of theelection. They only vote based on the affinity and advantage that they get in theform of service and assistance. Jenang’s role as a connector between the SukuAnak Dalam and Outside People can affect the intake of the Suku Anak Dalam’sdecision.Keywords: Suffrage, Suku Anak Dalam and Presidental Election.